Aspects of the geochemistry of the Karroo dolerites and basalts of the north-eastern Cape - Robey, Julian van Aardt (Rhodes University, Faculty of Science, Department of Geology, 1976)
The Birds River Gabbro Complex is intruded into sediments of the Karroo Stormberg Group in the area SW of Dordrecht in the northeastern Cape. A geochemical investigation, restricted to the igneous rock suite, gabbro-ferrogabbro-ferrotholeiite, presents new major-element data as well as data for twelve trace elements - Ba, Sr, Rb, Zr, Y, Nb , Zn, Cu, Ni, Co, V and Cr. The strong degree of differentiation of Kokstad-type tholeiitic magma in the Birds River intrusion, as noted by previous investigators, is revealed in variation diagrams in which data are plotted against a simple index of fractionation. Later differentiates are strongly enriched in Si, Ti, Fe, Na, K, P, Ba, Rb, Zr, Y, Nb, Zn and Cu but depleted in Mg, Ca, AI, Ni, Co and Cr. Extreme differentiation resulted in a strong depletion of Ti, Fe, P, Cu and V in the most highly evolved ferrotholeiites. Field evidence suggests the initial emplacement of strongly fractionated magmatic residua derived from fractional crystallization processes in a magma chamber at depth during cauldron subsidence of a mass of sediments within an annular fracture. These porphyritic, in part glassy, ferrotholeiites are enriched in Si, Na, K, Ba, Zr, Rb, Y, Nb and Zn and were engulfed by a later episode of renewed hypabyssal intrusive activity from the original source area. The younger gabbro was emplaced in a series of closely-spaced heaves or pulses of relatively undifferentiated Kokstad-type magma. The gabbro differentiated in place to form ferrogabbros which chemically closely approximate ferrotholeiite compositions. toidal facies. Residual liquids crystallized as a pegmatoidal facies. A simple fractional crystallization path, modelled on the assumption that the gabbro and ferrotholeiite form a continuous series, indicates that the least evolved ferrotholeiite can be derived from the initial gabbro composition by the fractionation of major amounts of plagioclase and pyroxene but lesser amounts of olivine. Crystallization and removal of magnetite and other Fe-oxides were relatively more important during the later stages of differentiation. The variation of major- and trace-elements in tholeiitic Karroo magma under conditions of strong differentiation at Birds River serves as a framework for the regional study of the geochemistry of other Karroo dolerites and volcanics of the north-eastern Cape. New geochemical data are presented for a sample of thirty chilled and coarse-grained Karroo dolerites collected throughout the north eastern Cape. For the most part, the chilled dolerites are relatively undifferentiated and the average composition differs only slightly from that determined by Walker and Poldervaart (1949). Variation diagrams reveal the steady increase in Si, Al, Ca, Na, K and P and the residual trace elements Ba, Zr, Rb, Y, Nb and Zn with increasing differentiation of the dolerites from more basic types. The concentrations of K, Ba and Rb are highly variable in some Karroo dolerites while new data suggest that Nb levels in the dolerites are low, being generally less than 10 ppm. The strong variation of the K-related elements (K, Ba and Rb) as well as the large ranges determined for certain inter-element ratios, such as K/Rb, Zr/Nb and K/Zr in the chilled Karroo dolerites, suggest that factors other than fractional crystallization processes need to be considered to account for individual variations. Little correlation exists between petrographic type as defined by Walker and Poldervaart (1949) and geochemical character. New geochemical data are also presented for ten Karroo basaltic lavas from the lowermost horizons of the lava sequence exposed in the Barkly East area. Major- and trace-element data indicate that these earliest Karroo extrusives are on average enriched in Si and Rb but depleted in Co and Ni when compared with the averaged chilled Karroo dolerite. Compared with basalts from Lesotho, the Barkly East basalts are enriched in Si but depleted in Ni and possibly Nb, Cu and V. The andesite is markedly enriched in Si, Na, K, Ba, Sr, Rb, Zr and Nb but depleted in Mg, Ca, V, Ni , Cu, Co and Cr. The subdued rate of Ni depletion and the absence of olivine as a major phenocryst phase in the series basalt to andesite, in the Barkly East area, suggests that differentiation trends may be controlled by the fractional crystallization of orthopyroxene and plagioclase, the two common phenocrysts present in these volcanics. The strong depletion of V and Cu in the andesite may indicate some magnetite removal during fractional crystallization.
Keywords: Diabase -- South Africa -- Cape of Good Hope; Basalt -- South Africa -- Cape of Good Hope; Geochemistry -- South Africa -- Cape of Good Hope